Effects of delay to stroke unit admission in patients with ischemic and hemorrhagic stroke. (31st January 2023) - Chen, Bing Yu; Gupta, Himanshu; Yacas, Clifford; Snyder, Hannah Elaine; Lee, Catherine; Bharwani, Aadil; Jung, Jessica; Suk, Yujin; Surendran, Vithushan; Chen, Steven; Zawawi, Ismaiel; Ma, Yu Fei; et al.
ABSTRACT: Objective: To determine the association between delay in transfer to a central stroke unit from peripheral institutions and outcomes. Methods: We conducted a retrospective cohort study of all patients with acute stroke, admitted to a comprehensive stroke center (CSC) from three emergency departments (EDs), between 2016 and 2018. The primary outcomes were length of stay, functional status at 3 months, discharge destination, and time to stroke investigations. Results: One thousand four hundred thirty-five patients were included, with a mean age of 72.9 years, and 92.4% ischemic stroke; 663 (46.2%) patients were female. Each additional day of delay was associated with 2.0 days of increase in length of stay (95% confidence interval [CI] 0.8–3.2, p = 0.001), 11.5 h of delay to vascular imaging (95% CI 9.6–13.4, p < 0.0001), 24.2 h of delay to Holter monitoring (95% CI 7.9–40.6, p = 0.004), and reduced odds of nondisabled functional status at 3 months (odds ratio 0.98, 95% CI 0.96–1.00, p = 0.01). Factors affecting delay included stroke onset within 6 h of ED arrival (605.9 min decrease in delay, 95% CI 407.9–803.9, p < 0.0001), delay to brain imaging (59.4 min increase in delay for each additional hour, 95% CI 48.0–71.4, p < 0.0001), admission from an alternative service (3918.7 min increase in delay, 95% CI 3621.2–4079.9, p < 0.0001), and transfer from a primary stroke center (PSC; 740.2 min increase in delay, 95% CI 456.2–1019.9, p < 0.0001). Conclusion: Delay to stroke unit admission in a system involving transfer from PSCs to a CSC was associated with longer hospital stay and poorer functional outcomes.